2017
DOI: 10.1093/ecco-jcc/jjx068
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Enteropathy Associated With SLCO2A1 Gene [CEAS]—Characterisation of an Enteric Disorder to be Considered in the Differential Diagnosis of Crohn’s Disease

Abstract: Small intestinal ulcers include mucosal damage caused by drugs, particularly nonsteroidal anti-inflammatory drugs [NSAIDs], infectious diseases, and idiopathic inflammatory bowel disease. Previously, a group of Japanese investigators reported an unusual and uncommon type of enteritis and referred to the condition as chronic nonspecific multiple ulcers of the small intestine [CNSU]. CNSU is characterised by chronic blood and protein loss through persistent small intestinal ulcers. Recently, four candidate mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 18 publications
4
50
0
Order By: Relevance
“…2a). The lesions occurred asymmetrically and independently of the mesenteric side and were endoscopically recognized as shallow ulcers with or without luminal narrowing, as reported previously [6, 12]. Ulcerative lesions varied in shape, being circular, oblique, or longitudinal, and ulcers occasionally formed a pseudodiverticulum (Fig.…”
Section: Resultssupporting
confidence: 66%
“…2a). The lesions occurred asymmetrically and independently of the mesenteric side and were endoscopically recognized as shallow ulcers with or without luminal narrowing, as reported previously [6, 12]. Ulcerative lesions varied in shape, being circular, oblique, or longitudinal, and ulcers occasionally formed a pseudodiverticulum (Fig.…”
Section: Resultssupporting
confidence: 66%
“…Subsequent reports stress distinction between CEAS and Crohn disease. [ 3 , 4 ] Agents used in chronic enteropathies such as inflammatory bowel disease, including 5-aminosalicylic acid, corticosteroids, azathioprine, and antitumor necrosis factor-α antibody, often are ineffective in CEAS, which frequently requires surgery. [ 1 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…The endoscopic findings of CEAS are characterized by multiple circular, longitudinal, or oblique shallow ulcers with discrete margins in the ileum (except for the terminal ileum), which resemble Crohn's disease or intestinal tuberculosis (3,6).…”
Section: Discussionmentioning
confidence: 99%
“…However, some patients with advanced disease develop abdominal pain with intestinal stenosis and require repeated surgeries (2). Because the appearance of ileal ulcers in patients with CEAS sometimes resembles that of Crohn's disease (CD) or intestinal tuberculosis, it is sometimes difficult to distinguish CEAS from them (3)(4)(5)(6). Umeno et al reported that CEAS is a hereditary disease caused by mutations in the SLCO2A1 gene (1,7).…”
Section: Introductionmentioning
confidence: 99%